EXILIOS Y ERRANCIAS EN LA OTRA ORILLA: APUNTES SOBRE LOS INTELECTUALES Y PERIODISTAS ESPAÃ‘OLES EN MARRUECOS (EL CASO DE TÃNGER) - Galindo, Juan Antonio GarcÃa (European Scientific Journal, ESJ, 2012)
The cosmopolitanism in the international city of Tangiers propitiated its economic, urban and cultural development far from the conflict being experienced in Spain. Attracted by the freedom and pluralism that was being enjoyed in the area; particularly because of ‘the myth of Tangiers’, as a paradise for writers’ and artists’ from around the world, many Spanish intellectuals and journalists found these lands to be the perfect place to live. The experience also enhanced their professional and creative lives. One of the main objectives of this work is to identify some of the protagonists and the different aspects between exiles and travelers. This study also highlights the existence of an exile towards the south, towards northern Africa, which was different to that moving towards Europe and Latin America.